Language Functions and Speech Acts in the Spoken Language of Elementary School Children on TikTok: A Case Study of @shabiraalula - Arini Hayati; Tri Indrahastuti; Tri Wahyuningsih; Hety Diana Septika (The Future of Education Journal, 2026)
This study was motivated by the increasing use of TikTok as a social media platform that has influenced children's communication patterns and language use in everyday life. It aims to describe the functions of language, the forms of illocutionary speech acts, and the reflection of children's pragmatic development in spoken language as represented in the TikTok content of @Shabiraalula&Ayah. The study employed a qualitative descriptive approach with a case study design. The data consisted of the spoken utterances of an elementary school-aged child extracted from three TikTok videos published on the @Shabiraalula&Ayah account. Data were collected through observation, documentation, and verbatim transcription, and subsequently analyzed using Halliday's theory of language functions and Searle's speech act theory within the frameworks of pragmatics and the sociolinguistics of digital media. The findings revealed five language functions: representational, interactional, heuristic, regulatory, and personal, with the representational function being the most dominant. Furthermore, the study identified assertive, expressive, and directive illocutionary speech acts, with expressive and assertive acts occurring most frequently. These findings indicate that children are able to use language contextually to convey information, express emotions, and establish social interactions within digital communication environments.